Towards a Different Knowledge: the Knjiženstvo Database and the Digitisation of Materials - Dojčinović, Biljana; Kolarić, Ana (Poznańskie Studia Slawistyczne, 2020)
The first part of this paper introduces the concept of digital humanities and the phases that some researchers note in the development of the humanities in new, digital media, as well as the role of digital humanities in the promotion of the marginalised literatures, particularly that written by women. The core example is the digital database Knjiženstvo, certain segments of which contain not only the data on the texts, but the digitised texts as well. In this paper, we pose the question on how databases can be involved in the creation of new knowledge at all educational levels. To this effect, we necessarily expand certain segments of the database to include those publications on which they already contain information. In relation to this, it has been observed that one of the greatest problems is the part of the database dealing with the periodicals – both women and feminist – and therefore, the second part of the paper is dedicated to this topic. We first analyze the terms women and feminist magazines, and afterwards, we consider the ways in which the materials from these periodicals could be gathered, classified and connected.